Simulacro e retórica : construção de ethé e do humor em artigos de opinião intergenéricos de Elio Gaspari - Castro, Gisely Gonçalves de (2015)
This research studies the construction of ethé and the humor in intergeneric opinion pieces written by Elio Gaspari. Based on the assumption that the construction of ethé of others emerges as the main argumentative strategy in these texts, we seek to verify how, by way of the use of rhetorical and humorous resources, Elio Gaspari constructs ethé of notorious Brazilian politicians. To such purpose, we selected eight opinion pieces in the form of e-mail published in the newspaper Folha de S. Paulo. Since the opinion pieces are structured by means of intergeneric process, they simulate e-mail exchanges with politicians and highlight the ethos of these personalities. For this reason, the opinion pieces are an appropriate place to study the concept of ethos. The relevance of this work is to expand the reflections about the use of argumentative strategies in opinion pieces. To conduct this study, we adopt the theoretical assumptions developed by researchers of the Rhetoric (Aristotle's Rhetoric and New Rhetoric), genres and humor. The analysis showed that, by way of the humor, Elio Gaspari constructs positive ethé of politicians who act as the senders of the e-mails and a negative ethos of those who act as the addressees. We also noticed that Elio Gaspari constructs not only ethé of other characters, but also representations of himself. In doing so, we conclude that the orator seeks to obtain the accession from his audience through the use of the ethos and the humor.